The The Development of Verbal Reasoning Assessment Instrument for Vocational School English Subject: Validity and Reliability - Cahyaningrum, Ryzka; Hartono, Rudi; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2023)
Reasoning is one of the important skills that should be mastered especially for vocational school students. Vocational school students are prepared to be worked ready, so they should have a clear reasoning. Reasoning that uses language as the main tool is called verbal reasoning. This study aimed to analyze the validity and reliability of the development of verbal reasoning assessment instrument. Quantitative was used as the method of study. 5 validators and 249 eleventh-grade students were involved as the research subjects. A verbal reasoning assessment instrument was shared with the students for the data collection. The technique of analysis used was content validity using Aiken’s V, construct validity using EFA and CFA, and reliability using KR-20. The results showed that content validity was validly stated by the mean of V value obtained was 0.853. EFA showed that the data was unidimensional. CFA indicated that the single-order model was supported by the data. Reliability indicated that the verbal reasoning assessment instrument was reliable by the ri obtained was 0.881 for the small scale and 0.822 for the large scale. Therefore, the verbal reasoning assessment instrument developed was valid and reliable. The teachers can use verbal reasoning assessment instrument to measure or evaluate students’ verbal reasoning in English subjects. Other than that, validity and reliability are the important parts in developing an instrument so this research may be used as a reference or information.